The Role of Administrative Law in Regulating Advanced Algorithms: A Legal Framework for Emerging Technologies - Rossa Ilma Silfia (International Publisher, 2025)
The integration of advanced algorithms and artificial intelligence (AI) into public administration has revolutionized decision-making processes, offering enhanced efficiency and scalability. However, this technological advancement presents significant challenges to traditional administrative law frameworks, particularly concerning transparency, accountability, and the protection of fundamental rights. The opacity of algorithmic decision-making, often referred to as the